ANALISIS KUALITAS PELAYANAN PERPUSTAKAAN TERHADAP KEPUASAN PENGUNJUNG PADA PERPUSTAKAAN SEKOLAH KRISTEN BASIC - Dachi, Markus Gunawan; Sugianto, Welly (LPPM Universitas Putera Batam, 2023)
Competition in the field of educational services, one of which relies on the ability of school libraries to provide satisfactory service quality to library visitors as service users. To measure the tangible or intangible quality of service, the level of visitor satisfaction can be measured. Libraries should regularly measure visitor satisfaction as an evaluation material to improve the quality of their services. This study was conducted to determine the influence of tangible, reliability, responsiveness, assurance, and empathy dimensions of service quality provided by the Basic Christian School library on visitor satisfaction. This study is a quantitative research model using the Service Quality method and linear regression. Service Quality is one of the methods used to measure visitor satisfaction with the quality of school library services. The measurement in the Service Quality method is divided into 5 dimensions: tangible, reliability, responsiveness, assurance, and empathy. In addition, regression analysis is conducted to determine the level of relationship between independent and dependent variables in this study. The research instrument used consists of 30 items of service quality and visitor satisfaction questionnaires adapted from Basuki (2019). The respondents in this study were 154 students from Basic Christian Junior High School and High School. The results of the study showed that variables with positive coefficients had an impact on increasing visitor satisfaction.